Variable thermo-physical characteristics of Carreau fluid flow by means of stretchable paraboloid surface with activation energy and heat generation. (June 2021) - Salahuddin, T.; Awais, Muhammad; Xia, Wei-Feng
Abstract: The present study is based on the flow of two dimensional Carreau fluid with heat generation and activation energy over the surface of paraboloid. The thermophysical properties such as viscosity, thermal conductivity and thermal diffusivity are chosen to be temperature dependent. The stretching in the fluid layers is presumed at the surface of object. This problem is modified by using law of conversation of momentum, mass, heat and concentration. The governing PDEs are transformed into dimensionless form by using appropriate similarity transformations. The numerical and graphical results are obtained via solving the ordinary differential equations by "RK4" technique with shooting method through MATLAB software. The impacts of key parameters on velocity, temperature and concentration fields are solved numerically and graphically. The power law index and variable viscosity parameter shows increment in velocity field. The temperature of fluid rises due to high values of heat source parameter while temperature shows reduction with Prandtl number. The cause of increment in concentration of fluid is due to activation energy and thermal diffusivity parameter.